Anthropometric Evaluation of pupils from APAE Araras-SP having Down Syndrome - Barbosa Ribeiro, Carolina; Tancredo Toledo, Mércia (O Mundo da Saúde, 2014)
Down syndrome is a genetic and metabolic disorder, which can affect nutritional status. Therefore, assessments and nutritional interventions are needed for these individuals to have a better quality of life, growth and development. The aim of the study was to evaluate the anthropometric status of pupils having Down syndrome assisted by the Association of Parents and Friends of Exceptionals (APAE) from Araras-SP, School unit. We collected weight, height, waist-hip ratio and skinfold in two stages: before and after a lecture series on healthy eating APAE had given to employees for a week. After the completion of the lecture cycle, 15 students were identified as being overweight according to Cronk curve, 18 students showed high levels of waist-hip ratio, according to the World Health Organization classification, and 11 students had a high fat percentage, according to the classification of Guedes protocol. The results obtained in this study showed that the lecture series intensified weight loss and reduction in the body mass index of students.